The Utilizing Whatsapp Application To Teach Speaking For Students Universitas Graha Nusantara - Harahap, Rosni (Yayasan Kajian Riset dan Pengembangan RADISI, 2023)
The pandemic has accompanied the education sector for about one year. Every student used to use mobile phone as the schools’ tool to have a home class learning. While, the signal of internet has not spread all over the villages in north Sumatera, they have difficulty to get the signal for joining the learning process. Among all the learning applications now, WhatsApp is the chosen application for the students in learning speaking class. The method uses in this research is descriptive method The data obtained from the true and recent condition of the third semester students of civics program at education and teaching faculty of Universitas Graha Nusantara. The result of this research tells the students’ real condition in learning speaking by using WhatsApp application for this pandemic situation. WhatsApp was chosen because there were many students lived in the remote area which has no internet signal. A researcher focuses on teaching the English basic for daily communication. The advantages of teaching speaking for non-English students give them supplies to communicate using English in this recent developing era.